Pergerakan Otonom Pasukan Berbasis Algoritma Boid Menggunakan Metode Particle Swarm Optimization - Syahri Mu'min; Mochammad Hariadi; Supeno Mardi Susiki Nugroho (Journal of Animation and Games Studies, 2015)
Real-Time Strategy game (RTS) is an interesting game, the screen is divided into the area map, units, and buildings. Play RTS games are generally made up of players who are positioned in a place on the map with multiple units or buildings, the player moves from one place to another. Group of characters or troops engaged in RTS games have broad approach, for this problem boids model. Ability Particle Swarm Optimization (PSO) to achieve optimum position creates the possibility to automatically generate non deterministic way a crowd of troops from certain positions. In this case, we focus on making the pattern moves are smooth and flexible realistic for virtual troops to take advantage of the computing facilities offered by PSO. That function is used to describe all types of objects in the system simulation, including static targets, static obstacles, and the troops which are considered as particles in finding ways to achieve the best solution. Keywords: autonomous agents, boid, particle swarm optimization, real-time strategy game.AbstrakPermainan real-time strategy (RTS) merupakan sebuah game yang menarik, layar dipisahkan menjadi peta area, unit, dan bangunan. Bermain game RTS umumnya terdiri dari pemain yang diposisikan di suatu tempat di peta dengan beberapa unit atau bangunan, pemain bergerak dari satu tempat ke tempat yang lain. Kelompok karakter atau pasukan yang bergerak dalam permainan RTS memiliki pendekatan luas, untuk masalah ini menggunakan model boids. Kemampuan Particle Swarm Optimization (PSO) untuk mencapai posisi optimum menciptakan kemungkinan untuk secara otomatis menghasilkan jalan non deterministic kerumunan pasukan dari satu posisi tertentu. Dalam kasus ini, kami fokus pada pembuatan pola bergerak yang halus dan fleksibel realistis bagi pasukan virtual dengan memanfaatkan fasilitas komputasi yang ditawarkan oleh PSO. Fungsi tersebut digunakan untuk menggambarkan semua jenis objek dalam sistem simulasi , termasuk target statis , hambatan statis , serta pasukan yang dianggap sebagai partikel dalam mencari cara untuk mencapai solusi terbaik.Kata Kunci : agen otonom, boid, particle swarm optimization, real-time game strategy